A primary standard for the measurement of alpha and beta particle surface emission rate from large area reference sources. (January 2016) - Ravindra, Anuradha; Kulkarni, D.B.; Joseph, Leena; Kulkarni, M.S.; Babu, D.A.R.
Abstract: A large area windowless gas flow multi wire proportional counting system for the calibration of large area reference sources has been developed as a primary standard at Bhabha Atomic Research Centre (BARC). The counting system consists of a multi wire proportional counter (MWPC), vacuum system, gas flow system and pulse processing units. The MWPC detector assembly consists of a vacuum tight aluminum enclosure, multi wire grid and sliding source tray. Various detector characteristics like operating characteristics curve, Fe-55 spectrum for beta discriminator threshold setting and dead time of the measurement system were studied and determined in order to achieve an optimized detection capability. The surface emission rates of different source strengths were measured and their relative combined standard uncertainties were determined. Large Area Sources Comparison Exercise (LASCE) was organized by International Committee on Radionuclide Metrology (ICRM) working group and coordinated by National Institute for Ionising Radiation Metrology (ENEA), Italy, to demonstrate equivalence of surface emission rate measurements at the international platform. BARC participated in the programme and the results of LASCE are also discussed in this paper. Highlights: Large area window less gas flow multi wire proportional counting system was set up. Studied various detector working parameters for optimized detection capability. Surface emission rate measurements of large area beta sources were measured. Large area reference sources for calibration of surface contamination monitors. Equivalence of surface emission rate measurements was demonstrated by LASCE.